Survival and periapical health after root canal treatment with carrier‐based root fillings: five‐year retrospective assessment. (24th March 2017) - Pirani, C.; Friedman, S.; Gatto, M. R.; Iacono, F.; Tinarelli, V.; Gandolfi, M. G.; Prati, C.
Abstract: Aim: This retrospective study explored survival and periapical healing outcomes in teeth root filled with Thermafil obturators. Methodology: Root canals of 213 teeth (94 subjects, mean age 48 ± 13 years), instrumented with a step‐down technique, irrigated with 5% NaOCl and 10% EDTA and filled with Thermafil and AH Plus sealer, were involved in a recall programme. Teeth were retrospectively re‐examined after 5 ± 1 years in a controlled environment. Clinical and radiographic data that were collected included the following: preoperative Periapical Index (PAI) score and signs/symptoms, treatment type, root filling length and presence/absence of voids, restoration type, follow‐up PAI score and signs/symptoms. Teeth were considered 'healthy' (PAI ≤ 2, no signs/symptoms) or 'diseased' (PAI ≥ 3, signs/symptoms present, retreated, extracted for endodontic reasons). Two PAI‐calibrated examiners assessed outcomes blinded to preoperative status. Bivariate and multilevel analyses were performed at level of patient and tooth (α = 5%). Results: Of 213 teeth treated, 187 (88%) survived and 26 were extracted, six (3%) for persistent endodontic infection (considered 'diseased'), and 20 (9%) for root fracture, periodontal disease or coronal fracture (excluded from analysis). Whilst survival was significantly associated with tooth type ( P = 0.015), type of treatment ( P = 0.012) and pulpal/periapical diagnosis ( P = 0.035), none of these variables were substantiated as survival predictors by the multilevel analysis. A total of 164 of 193 teeth (85%) were assessed as 'healthy', with significantly higher (chi‐square; P < 0.04) 'healthy' rates for teeth with PAI score ≤2 and root fillings of adequate length. Multilevel analysis identified PAI score ≤2 ( P = 0.002) as the only predictor of periapical health. Conclusions: In this 5 ± 1 year retrospective assessment, survival and healing rates after root canal treatment with Thermafil root fillings were comparable to those previously reported for conventional root filling techniques.